On the Heterogeneous Distribution of Secondary Precipitates in Friction-Stir-Welded 2519 Aluminium Alloy - Ivan S. Zuiko (Metals, 2022)
The macro-scale distribution of secondary precipitates in friction-stir-welded 2519 aluminium alloy was studied. It was found that precipitation pattern essentially varied within the stir zone in terms of volume fraction, size, and even preferential concentration of the particles, either at grain boundaries or within the grain interior. This effect was attributed to local variations in welding temperature and cooling rate, which led to complex precipitation phenomena including coarsening, dissolution, and partial reprecipitation. Specifically, the precipitation coarsening was most pronounced at the weld root due to the lowest welding temperature being in this area. On the other hand, the highest welding temperature at the upper weld surface enhanced the dissolution process. The reprecipitation phenomenon was deduced to be most prominent in the weld nugget due to the slowest cooling rate being in this microstructural region.